KEY DETERMINANTS DRIVING AUDITEE SATISFACTION-TECHNICAL AUDIT DOMINANCE AND RESPONSIVENESS BACKFIRE IN MALUKU - Leiwakabessy, Theophilia Fina Febrione; Lewaru, Trisna Sary; Kriswantini, Dwi; Putuhena, Hempry; Fauzan, M Rifkhi (Universitas Riau, 2026)
This study examines the influence of audit quality dimensions on auditee satisfaction in the Indonesian public sector, specifically within the Maluku Provincial Government. Using the AUDITQUAL framework, this quantitative study employs a survey design with 138 respondents from Regional Government Organizations (OPD). Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the relationships between six audit quality dimensions (reputation, expertise, capability, independence, responsiveness, and empathy) and auditee satisfaction. Four of six hypotheses were supported. Expertise emerged as the strongest predictor of auditee satisfaction, followed by capability, reputation, and independence. Interestingly, responsiveness showed a significant negative relationship with auditee satisfaction, while empathy had no significant effect. This research addresses the gap in auditee perspective studies in Indonesian public sector auditing, revealing that technical quality dimensions outweigh service quality in determining satisfaction, contrary to private sector findings. The negative effect of responsiveness provides new insights into auditor-auditee dynamics in governmental contexts. Auditee satisfaction is more determined by auditor technical quality compared to relational quality. The stewardship theory framework that emphasizes that auditors as stewards need to build trust through professional competence and independence, not through emotional closeness that can threaten objectivity